LOCAL GROUPS CLAIM VICTORY AT END OF LNG PROJECT - Environmental Defense Center (EDC); Santa Barbara Channelkeeper (SBCK) (Environmental Defense Center (EDC))
The Environmental Defense Center (EDC) and Santa Barbara Channelkeeper (SBCK) celebrated today after learning that the application for Northerns tar's Clearwater Port Liquefied Natural Gas (LNG) project was terminated by the California State Lands Commission.